Pelatihan Media Sosial WhatsApp, Facebook, dan TikTok Untuk Promosi Produk Koperasi Syariah Domas Surya Berkemajuan - Fadilla Bagas Rasyadha; Muhammad Rifa'i Alliansyah (Jurnal Bina Ilmu Cendekia, 2026)
Koperasi Konsumen Syariah Domas Surya Berkemajuan in Domas Village, Pontang District, Serang Regency, Banten, is composed of small traders and farmers whose flagship products include processed milkfish (bandeng) and bontot, a local fish cake made from payus fish. The partner's main problems are limited awareness of the importance of social media for promotion and limited skill in using WhatsApp, Facebook, TikTok, and Instagram to market products. This community service activity aimed to improve members' understanding and technical skills in content creation and social media advertising. The method consisted of a field assessment, socialization on the importance of social media, and hands-on training in content creation using Canva and CapCut, conducted in Domas Village in August 2023 in partnership with the sharia cooperative and LAZISMU. The results show that all participating members demonstrated improved understanding of social media's promotional potential and were able to independently produce simple photo, video, and advertising content for WhatsApp, Facebook, TikTok, and Instagram. The activity is expected to encourage cooperative members to market their products independently and sustainably through digital platforms.